Research on the Application and Information Disclosure of Third Level Input Values in Fair Value Measurement - Li, Ding (International Journal of Global Economics and Management, 2026)
Fair value measurement is a core measurement attribute of modern financial accounting. In its hierarchical division, the third level input value has become a key and difficult point in practical application and information disclosure due to its dependence on unobservable data and valuation techniques. This article is based on the relevant regulations of IFRS 13 and CAS 39 in China, using literature research and normative research methods to analyze the operational difficulties and disclosure status. Research has found that Chinese enterprises have problems with inconsistent valuation techniques, subjective parameter settings, and insufficient data verifiability in the application of this input value. Disclosure also has deficiencies such as insufficient content, vague expression, poor comparability, and lack of sensitivity analysis. The main causes are the strong principle guidance of the standards, insufficient valuation ability of enterprises, imperfect external environment, and lack of regulatory strength. This article proposes to refine practical guidelines, enhance the level of enterprise valuation, build a unified valuation database, strengthen regulatory accountability, and improve its application and disclosure quality. The research conclusion can provide reference for enterprises to standardize operations and regulatory agencies to optimize policies, helping to improve the relevance and reliability of financial reporting information.